Outcomes of meso-Rex bypass for prehepatic portal hypertension in pediatric patients - Pierre Jean Aurelus; Sofia Brenes Guzmán; Gloria Abigail Medrano De La Rocha; Juan Carlos Nuñez Enríquez; Jose Luis González Chávez; Jairo Candido Torres Aguilera; Hermilo De La Cruz Yañez (Elsevier, 2024)
Portal hypertension in pediatric patients is often associated with prehepatic portal hypertension (PHPH), frequently linked to thrombosis and cavernomatous degeneration of the portal vein (CDVP). This study evaluates the efficacy of the MesoRexBypass (MRB) in managing PHPH and associated thrombosis. Methods: A retrospective prognostic cohort design was employed to analyze the clinical outcomes of nine pediatric patients who underwent MRB between 2020 and 2022. Clinical and surgical variables were examined, including graft type, surgical time, and complications. Postoperative follow-up confirmed MRB functionality. Results: The MRB proved highly successful, with improved clinical parameters observed in all patients. Significant reductions in gastrointestinal bleeding, esophageal varices, and hypertensive gastropathy were observed postoperatively. Thrombocytopenia and liver enzyme levels showed substantial improvement, indicating enhanced liver function and amelioration of hypersplenism. The MRB's adaptability was demonstrated using autologous grafts and various graft sources.One patient experienced shunt thrombosis, another experienced minor gastrointestinal bleeding, and another died. The MRB exhibited a high success rate and few complications. Conclusion: The MRB is an effective and versatile surgical technique for managing PHPH in pediatric patients. This study emphasizes its promising outcomes and suggests its potential for enhancing treatment approaches and quality of life in this patient population. Further research with larger cohorts is needed to strengthen the evidence presented. The MRB holds promise as a valuable addition to the management of PHPH in children. Level of Evidence IV.